Paradigma Teknologi Informasi Menembus Ruang Dan Waktu Serta Pemanfaatannya Untuk Dunia Pendidikan Dan Bisnis Gaya Hidup - Wandyatmono, Joko (APMMI - Asosiasi Profesi Multimedia Indonesia, 2009)
ABSTRACT: Information Technology is a combination of electronic technology and telecommunications technology. Informatics is part of the science of electronics. While the science of electronics is the branch of science that studies the techniques and utilize the electrons contained in all objects and play a role in all natural phenomena called electricity. Electrical engineering regard the electron as an agent or principal actors in the process over a variety of energy from one form to another, or cue signal processing as well as in the processing and presentation of information. Individual properties as well as properties in combination with a carefully excavated, processed and utilized for the benefit of man. Observed is the nature outside. Related to the dynamics of electrons which appear as outer nature is the voltage, current and power.Keywords: information, telecommunicationÂ ABSTRAKSI : Teknologi Informasi adalah gabungan dari teknologi elektronika dan teknologi telekomunikasi. Informatika merupakan bagian dari ilmu elektronika. Sedangkan ilmu elektronika adalah cabang ilmu teknik yang mempelajari dan memanfaatkan elektron yang terdapat didalam semua benda dan yang berperan dalam semua gejala alam yang disebut kelistrikan. Teknik elektro memandang elektron sebagai agen atau pelaku utama dalam proses alih ragam energi dari satu bentuk ke bentuk lain, pengolahan sinyal atau isyarat serta dalam pengolahan dan penyajian Informasi. Sifat individual serta sifat dalam gabungan dengan cermat digali, diolah dan dimanfaatkan untuk kepentingan manusia. Yang diamati adalah sifat luarnya. Berkaitan dengan dinamika elektron yang tampil sebagai sifat luar adalah tegangan, arus dan daya listrik.Kata kunci: informasi, telekomunikasi